2015
DOI: 10.1371/journal.pone.0132974
|View full text |Cite
|
Sign up to set email alerts
|

The Semen pH Affects Sperm Motility and Capacitation

Abstract: As the chemical environment of semen can have a profound effect on sperm quality, we examined the effect of pH on the motility, viability and capacitation of human sperm. The sperm in this study was collected from healthy males to avoid interference from other factors. The spermatozoa cultured in sperm nutrition solution at pH 5.2, 6.2, 7.2 and 8.2 were analyzed for sperm total motility, progressive motility (PR), hypo-osmotic swelling (HOS) rate, and sperm penetration. Our results showed that these parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
104
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 45 publications
(51 reference statements)
8
104
1
2
Order By: Relevance
“…The results of our study showed that pH e 8.0 with OFCM led to a decrease in all motility parameters except for WOB although the main factor responsible was the addition of OFCM. Some authors36 observed that a pH e below 7.2 affected sperm motility and capacitation but there was no effect between pH e 7.2 and 8.2. This apparent inconsistency with our results could be explained by the different experimental conditions used in the studies, the sperm source (human sperm vs .…”
Section: Discussionmentioning
confidence: 98%
“…The results of our study showed that pH e 8.0 with OFCM led to a decrease in all motility parameters except for WOB although the main factor responsible was the addition of OFCM. Some authors36 observed that a pH e below 7.2 affected sperm motility and capacitation but there was no effect between pH e 7.2 and 8.2. This apparent inconsistency with our results could be explained by the different experimental conditions used in the studies, the sperm source (human sperm vs .…”
Section: Discussionmentioning
confidence: 98%
“…Zanaty et al (29), showed a direct relationship between viscosity of semen and semen zinc level. Weak sperm mobility and production was related to lower level of zinc in semen plasma in infertile males (30). As various relevancies were shown in different investigations, a number of studies did not find any relationship between semen plasma zinc level and 4…”
Section: Discussionmentioning
confidence: 91%
“…The semen extender, therefore, should be formulated to closely resemble the environment of sperm cells in the body. Any change in pH that occurs during the sperm cryopreservation process could affect the rates of metabolism, motility and viability of sperm as well as its capability to fertilise the oocytes (Bonato et al, 2012;Zhou et al, 2015). A number of pH regulators, such as bicarbonate, sodium citrate, Hepes or Tris, have been added into the extender to control the pH of the medium (Gadea, 2003).…”
Section: Discussionmentioning
confidence: 99%